2012
DOI: 10.1007/s00114-012-0961-x
|View full text |Cite
|
Sign up to set email alerts
|

Inbreeding and the evolution of sociality in arthropods

Abstract: Animals have evolved strategies to optimally balance costs and benefits of inbreeding. In social species, these adaptations can have a considerable impact on the structure, the organization, and the functioning of groups. Here, we consider how selection for inbreeding avoidance fashions the social behavior of arthropods, a phylum exhibiting an unparalleled richness of social lifestyles. We first examine life histories and parental investment patterns determining whether individuals should actively avoid or pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 96 publications
0
28
0
Order By: Relevance
“…There are widespread theoretical predictions and growing empirical evidence that insects have evolved mechanisms to avoid breeding with close kin [7], [20], [27], [33]. Pre-copulatory kin recognition has been reported for several insect and mite species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are widespread theoretical predictions and growing empirical evidence that insects have evolved mechanisms to avoid breeding with close kin [7], [20], [27], [33]. Pre-copulatory kin recognition has been reported for several insect and mite species.…”
Section: Discussionmentioning
confidence: 99%
“…One of the many proposed explanations for polyandry is that it functions as a mechanism to avoid inbreeding [3], [4], [5], [6]. A growing number of empirical studies have reported that inbreeding may have profound impact on the fitness-related traits of insects [7]. Inbreeding can have strong negative effects on fitness at all life stage, including larval development time [8], [9], survival [10], [11], adult body size and mass [12], [13], [14], adult lifespan [12], [15], fecundity [15], [16], [17], fertility [18], [19], [20], and even immune function [21].…”
Section: Introductionmentioning
confidence: 99%
“…Most social birds, mammals and insects maintain premating dispersal or other inbreeding avoidance mechanisms and outcrossing mating systems (Pusey, 1987;Pusey & Wolf, 1996;Tabadkani et al, 2012). Thereby, they avoid the immediate fitness cost caused by the expression of deleterious alleles (Charlesworth & Willis, 2009;Wang, Hill, Charlesworth, & Charlesworth, 1999), which is expected under inbreeding even if some of the genetic load is purged by natural selection (Crnokrak & Barrett, 2002;Hedrick, 1994).…”
Section: Consequences Of Low Genetic Diversitymentioning
confidence: 99%
“…In addition, some social species show female-biased sex ratio (Bourke, 1997;Hamilton, 1967;Nomura & Takahashi, 2012;West, 2009), and the social insects (bees, ants, and wasps, thrips and some bark beetles) are haplodiploid, which further decreases Ne (Hedrick & Parker, 1997). Most social species maintain an outcrossing mating system through sex-biased dispersal (Clobert, Danchin, Dhondt, & Nichols, 2001;Pusey, 1987;Tabadkani, Nozari, & Lihoreau, 2012;Wilson, 1971), and thereby reduce the risk of inbreeding. In contrast, sociality in a number of taxa involves a regular inbreeding or even an obligatory inbreeding mating system.…”
mentioning
confidence: 99%
“…In the Hymenoptera, many pre-copulatory mechanisms exist to limit inbreeding, including dispersal from the natal nest (Tabadkani et al, 2012), cuticular hydrocarbon profiles delineating nestmates from non-nestmates (Oppelt et al, 2008), and hereditary blends of pheromone components indicative of family groups (Herzner et al, 2006). The avoidance of sibling gynes by D. maculata males indicates that male sense gyne relatedness through olfactory cues.…”
Section: Hypothesis 2: Males Prefer Non-sibling Gynes Based On Olfactmentioning
confidence: 99%